Technologies and Solutions to Manage Plastic Waste in Small and Remote Islands : Using the Technology Options for Plastic waste in Island Contexts (TOPIC) Toolbox for Islands in Malaysia - World Bank (Washington, DC, 2022)
The rising production and consumption of plastic combined with mismanagement of plastic waste is leading to significant pollution of marine and coastal areas. Addressing plastic waste on islands is crucial because of their roles as both receptors and contributors. While there is no single solution to turn the tide on plastic pollution for small and remote islands, a combination of technologies and other upstream and downstream solutions can help these communities effectively manage plastic waste, safeguarding their valuable ecosystems and livelihoods. New innovative technologies to treat plastic waste only work effectively in specific island contexts with viability impacted by many different aspects including the volumes and type of plastic waste, existing solid waste management systems, infrastructure, and community awareness. In addition to treatment technologies, other solutions need to be considered such as reducing the plastic input to islands upstream, before it becomes plastic waste, as well as sorting and then transporting plastic waste to a viable recycling market. This study combines a global assessment of plastic waste management on islands with a review of existing technologies and their viability in island contexts to develop the Technology Options for Plastic waste for Island Contexts (TOPIC) Toolbox which was then piloted on five islands in Malaysia. The TOPIC Toolbox supports island decision-makers in identifying technologies and a potential mix of technologies and other solutions to treat plastic waste for their island.